Primary Intraosseous Meningioma: CT and MRI Appearance - Tokgoz, Nil; Oner, Yusuf A.; Kaymaz, Memduh; Ucar, Murat; Yilmaz, Guldal; Tali, Turgut E. (American Journal of Neuroradiology, 2005)
Summary: Benign primary intraosseous meningioma presenting with osteolytic skull lesion and soft-tissue component is rare. CT and MR imaging of a patient with frontoparietal scalp swelling showed an osteolytic intracalvarial lesion with an extradural soft-tissue component. Following wide surgical resection, the histological examination revealed an intraosseous chordoid meningioma. The clinical and radiological findings of primary intraosseous meningioma are discussed and the relevant literature is reviewed.